The king and the land a geography of royal power in the biblical world - Russell, Stephen C. (New York, NY Oxford University Press, 2017)
Solomon's temple : on space, power, and ancient evidence -- David's threshing floor : on royal dedication of land to the gods -- Jehu's dung heap : on royal decommissioning of religious space -- Absalom's gate : on royal navigation of collective urban politics -- Hezekiah's tunnel : on royal shaping of the water supply system
Includes bibliographical references (pages [205]-258) and indexes
Keywords: Bible -- History of Biblical events; Bible -- History of Biblical events; Kings and rulers -- Biblical teaching; Kings and rulers, Ancient